Moving Memories of Slavery among West African Migrants in Urban Contexts (Bamako, Paris) - (:unkn) unknown (My University, 2013)
“Moving memories of slavery” are those memories of internal African slavery that move with West African migrants to urban areas. Different types of mobility towards and within urban contexts can be considered as non-discursive, embodied forms of ‘memory work’ of slavery. The focus is on how Fulɓe (and Soninke) migrants in Bamako and Paris ‘move with’ or ‘move back into’ slave status on specific moments in space and time. Even though cities offer opportunities to silence memories about their slave past, this can be only temporal and necessarily intersects with age, class, gender, etc. The data presented demonstrate that under specific conditions, urban contexts can also reproduce – even if temporarily – stigma, labour divisions and hierarchical inequalities related to the memory of slavery.
Keywords: African Research